Differential Myotoxic and Cytotoxic Activities of Pre‐synaptic Neurotoxins from Papuan Taipan (Oxyuranus scutellatus) and Irian Jayan Death Adder (Acanthophis rugosus) Venoms. (23rd February 2013) - Chaisakul, Janeyuth; Parkington, Helena C.; Isbister, Geoffrey K.; Konstantakopoulos, Nicki; Hodgson, Wayne C.
Abstract Pre‐synaptic PLA2 neurotoxins are important components of many Australasian elapid snake venoms. These toxins disrupt neurotransmitter release. Taipoxin, a pre‐synaptic neurotoxin isolated from the venom of the coastal taipan (Oxyuranus scutellatus), causes necrosis and muscle degeneration. The present study examined the myotoxic and cytotoxic activities of venoms from the Papuan taipan (O. scutellatus) and Irian Jayan death adder (Acanthophis rugosus), and also tested their pre‐synaptic neurotoxins: cannitoxin and P‐EPTX‐Ar1a. Based on size‐exclusion chromatography analysis, cannitoxin represents 16% of O. scutellatus venom, while P‐EPTX‐Ar1a represents 6% of A. rugosus venom. In the chick biventer cervicis nerve‐muscle preparation, A. rugosus venom displayed significantly higher myotoxic activity than O. scutellatus venom as indicated by inhibition of direct twitches, and an increase in baseline tension. Both cannitoxin and P‐EPTX‐Ar1a displayed marked myotoxic activity. A. rugosus venom (50–300 μg/ml) produced concentration‐dependent inhibition of cell proliferation in a rat skeletal muscle cell line (L6), while 300 μg/ml of O. scutellatus venom was required to inhibit cell proliferation, following 24‐hr incubation. P‐EPTX‐Ar1a had greater cytotoxicity than cannitoxin, inhibiting cell proliferation after 24‐hr incubation in L6 cells. Lactate dehydrogenase levels were increased after 1‐hr incubation with A. rugosus venom (100–250 μg/ml), O. scutellatus venom (200–250 μg/ml) and P‐EPTX‐Ar1a (1–2 μM), but not cannitoxin (1–2 μM), suggesting venoms/toxin generated cell necrosis. Thus, A. rugosus and O. scutellatus venoms possess different myotoxic and cytotoxic activities. The proportion of pre‐synaptic neurotoxin in the venoms and PLA2 activity of the whole venoms are unlikely to be responsible for these activities.